A NEW METHOD OF TREATING PNEUMONIA COMPLICATED BY AN ABSCESS IN PATIENTS AFTER COVID-19 - Shadmanov, A.K.; Mirshaval, J.H.; Okhunov, A.O.; Bobokulova, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The effects of SARS-CoV-2 (COVID-19) have increasingly challenged physicians in recent years. The variation of their possible effects is endless. However, lung damage as a primary target organ in coronavirus infection remains a major problem, which often takes the form of a fatal process, determining the further health condition of the patient in general. Therefore, our study aimed to develop and evaluate the effectiveness of endovascular catheter therapy in patients with abscessed pneumonia who had had COVID-19. Methods. This paper presents data on the comprehensive examination and treatment of 67 patients with abscessed pneumonia after COVID-19 for the period from 2020 to 2022. Results. The two-stage injection of drugs should also be referred to the peculiarities of our developed method of treatment of abscessed pneumonia in patients who suffered from COVID-19. At the first stage (1-2 days) - drugs that improve microcirculation and detoxifying agents. In the second stage, we supplemented the treatment with protein-synthetic enhancement agents. Antibacterial therapy was carried out by bolus injection of drugs directly into the lung tissue. Conclusion. Application of the developed method of pulmonary endotheliitis treatment in patients with abscessed pneumonia after COVID-19 allowed reducing the period of catheter therapy and accelerating the process of purulent-destructive process restriction, increasing the rate of complete and clinical recovery by 15,6%, reducing the rate of chronicity by 5,5% and mortality by 15,7%.